Update on the efficacy, effectiveness and safety of artemether–lumefantrine combination therapy for treatment of uncomplicated malaria - Byakika-Kibwika, Pauline (Dove Medical Press, 2010)
Artemether–lumefantrine is one of the artemisisnin-based combination therapies recommended for treatment of uncomplicated falciparum malaria. The drug combination is highly efficacious against sensitive and multidrug resistant falciparum malaria. It offers the advantage of rapid clearance of parasites by artemether and the slower elimination of residual parasites by lumefantrine. The combination can be used in all populations except pregnant mothers in the first trimester where safety is still uncertain. There are still concerns about safety and pharmacokinetics of the drug combination in children, especially infants, pregnant mothers and drug interactions with mainly non-nucleoside reverse transcriptase inhibitors and protease inhibitors used for HIV therapy.